Fluorescent in Situ Hybridization and Real-Time Quantitative Polymerase Chain Reaction to Evaluate HER-2/neu Status in Breast Cancer - Fatemeh Homaei Shandiz; Azar Fani; Sepideh Shakeri; Maryam Sheikhi; Abouzar Ramezani Farkhani; Arezoo Shajiei; Hossein Ayatollahi (Iranian Society of Pathology, 2017)
Background:Breast cancer remains the most common and second lethal cancer in females. HER-2/neu is one of the most important amplified oncogene in breast cancer. The amplification of HER-2 is correlated with decreased survival, metastasis, and early recurrence.  The amplification of HER-2/neu gene and synthesis of the protein are reported in 10%-34% of breast cancer cases associated with tumor size, advanced tumor stage, high-grade tumor, young age at diagnosis, absence of steroid hormone receptor, and lymph node involvement. Methods: Fluorescence in situ hybridization (FISH) and immunohistochemistry (IHC) methods are options to evaluate HER-2 expression. The current study aimed at identifying the correlation between FISH and real-time polymerase chain reaction (PCR) in measuring HER-2 expression. Results: The study investigated the performance of the real-time PCR as measured against FISH method in IHC +2 borderline cases. In a total of 120 IHC 2+ samples, 58.3% were negative and 41.6% positive for HER-2 gene, confirmed by FISH as a gold standard method. The real-time PCR ratio was HER-2 gene by FISH as a gold standard assay. Conclusion: Despite the fact that real-time PCR is a promising method to evaluate HER-2 over expression and a supplementary array to FISH, according to the results of the present study it cannot be utilized instead of gold standard techniques; therefore, additional studies should be carried out to appraise the value of this method to evaluate HER-2 over expression.